A monochromatic x-ray irradiation system for in vitro studies at synchrotron beamlines. (8th September 2016) - Niestroj, M; Bewer, B; Mousseau, D D; Chapman, D; Chen, J; Hormes, J
Abstract: The use of synchrotron light in radiobiological keV x-ray in vitro studies has been accompanied by compromises in culture conditions and sample handling procedures. The presented monochromatic x-ray system bridges the gap between synchrotron science and cell biology by facilitating the irradiation of adherent cells uninterruptedly maintained under cell type-specific conditions throughout the entire experiment. The system for horizontal irradiations consists of a single crystal Laue monochromator, a beam monitor, and a scanning sample stage. As implemented at the BMIT-BM beamline, the system enables homogeneous cell culture irradiations with intense and purely monochromatic x-ray beams (10–30 keV). The first MCF-7 dose-response study demonstrates how the establishment of a stress-minimized experimental procedure leads to accurate and precise in vitro irradiation results. The cell survival as a function of the surface dose is well described by a first-order exponential decay, indicating that the cellular damage induced by 11.9 keV x-rays is comparable to the lethal effects caused by high linear energy transfer particles. The system design opens up the pathway for combined live-cell imaging and monochromatic keV x-ray applications, while the implementation of the system at insertion device beamlines can help to establish novel investigations on the fundamental role of photonactivation agents in an energy regime up to 100 keV.